Upaya Peningkatan Pemahaman Remaja Dari Bahaya Seks Bebas Guna Pencegahan HIV/AIDS Dengan Video Animasi - Ulfah Jamil, Maria; Rahmawati, Ai; Mulyana, Asep; Sopiah Suryani, Iis; Mulyana, Hilman; Nurdianti, Reni; Nurakilah, Heni; Daryanti, Eneng (Universitas Bhakti Kencana, 2024)
Adolescence is a period of transition from childhood to adulthood, which includes all the development experienced in preparation for entering adulthood. These developmental changes include physical, psychological and psychosocial aspects. The most difficult task of adolescent development is related to social adjustment. Teenagers who have to adjust to opposite sex relationships that have never existed before so they adjust to adults outside the family and school environment. Teenagers spend more time with friends, so the influence of peers on attitudes, conversations, interests, appearance and behavior is greater than the influence of family. The problems faced by teenagers originate from changes due to the maturation of reproductive organs which are often unknown to teenagers themselves. These changes can provide certain psychological and emotional impulses which often cause confusion in teenagers. This can cause teenagers to search for self-identity, develop a desire to date, have a deep sense of love, develop the ability to think abstractly and fantasize about sexual activities with the opposite sex. Community service carried out for teenagers at MTsN 2 Tasikmalaya City through providing education about the importance of knowing about free sex in order to prevent sexually transmitted diseases which can lead to HIV/AIDS with animated videos. The results of the counseling showed that MTsN 2 Tasikmalaya City students understood the importance of protecting themselves from free sex in order to avoid contracting HIV/AIDS.